IMPLEMENTASI PENDAMPINGAN BRANDING BERBASIS MEDIA PROMOSI CETAK UNTUK PENGUATAN IDENTITAS USAHA UMKM BTPN SYARIAH DI MMS SEMAMPIR 2 SURABAYA - Azza Nur Lailiyah; Irma Kurniasari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
A business identity strengthening mentoring program for BTPN Syariah customers at MMS Semampir 2 Surabaya was implemented to improve the branding capacity and competitiveness of MSMEs. This activity involved university students as facilitators who provided structured training on developing business identities, including name selection and banner design. The mentoring was conducted weekly for four months through assessments, material delivery, practice, and evaluation. The implementation results showed a significant increase in customer understanding and skills in building a visual business identity. Customers were able to produce informative and professional banners that reflect the character of the business, thereby increasing visibility and image in the eyes of consumers. The banner installation also resulted in an increase in the number of customers and awareness of the importance of branding in business development. Overall, this program contributes to the empowerment of MSMEs through the strengthening of sustainable and more competitive brand identities.